Study in the impact of quaternized graphene oxide (QGO) composition as modifier on the chemical, physical, mechanical, and performance properties of polyvinylidene fluoride (PVDF)-based nanocomposite membrane - Ashabul Kahfi; Kusumawati, Nita; Setiarso, Pirim; Supari Muslim; Sinta Anjas Cahyani; Nafisatus Zakiyah (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Polyvinylidene Fluoride (PVDF) membranes were modified with quaternized graphene oxide (QGO) synthesized from graphene oxide and quaternized ammonium groups. PVDF/QGO membranes were created by blending PVDF and 0.01-0.05 g QGO via phase inversion. FTIR confirmed the successful QGO incorporation. PVDF/QGO membranes exhibited increased mechanical stiffness. Meanwhile, SEM revealed asymmetric morphology with surface and internal pores. AFM showed the membrane with 0.05 g and QGO had the highest surface roughness of 101.2 nm, which increased filtration area and flux. QGO improved hydrophilicity through hydroxyl and quaternary ammonium groups, enhancing water flux up to 1208 Lm?2h?1 for 0.05 g QGO. Cu2+ rejection increased to 75% for 0.05 g QGO membrane due to chelation and adsorption effects. PVDF/QGO membranes displayed bacterial growth inhibition, unlike pristine PVDF. The inhibition zone diameter increased with more QGO, indicating improved antibacterial activity. Overall, this study demonstrated that QGO improved PVDF membranes' hydrophilicity, antibacterial properties, and mechanical strength.